Irregular Migrations in Bosnia and Herzegovina: Detention, Readmission and Return (Kriminalističke teme, 2023)
Since early 2018, Bosnia and Herzegovina has been facing an increased influx of migrants who enter the country illegally, call for international protection, but do not want to stay in Bosnia and Herzegovina because the highly developed countries of the European Union are their final destination. Irregular migrations faced by the member states of the European Union as well as the countries of the Western Balkans had many political, social, cultural and security implications. The European Union, determined to stop irregular migration, adopted a series of strategic documents, including the Action Plan for the Western Balkans, where one of the key elements of that plan is the return of irregular migrants to their countries of origin. However, the question arises to what extent Bosnia and Herzegovina has built its strategic, legal and institutional framework that would enable the efficient removal of irregular migrants from its territory. The aim of this paper is to review the approach to the detention of irregular migrants and its importance in these processes, as well as the importance of the readmission and return of irregular migrants in the comprehensive migration management process. The paper will analyse the data on the measures taken against irregular migrants in Bosnia and Herzegovina presented through the decisions on expulsion and detention, make a presentation of concluded agreements on readmission with other countries, and analyse data on the activities undertaken on the implementation of agreements on the readmission and removal of irregular migrants from the territory of Bosnia and Herzegovina.